2016
DOI: 10.1016/j.it.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Functions of H3K27Me3 Demethylases in Immune Cell Differentiation

Abstract: The trimethylation of histone H3 lysine 27 (H3K27Me3) contributes to gene repression, notably through recruitment of Polycomb complexes, and has long been considered essential to maintain cell identity. Whereas H3K27Me3 was thought to be stable and not catalytically reversible, the discovery of the Utx and Jmjd3 demethylases changed this notion, raising new questions on the role of these enzymes in gene expression and cell differentiation. Recent studies have demonstrated critical roles for Utx and Jmjd3 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 86 publications
(139 reference statements)
2
35
0
Order By: Relevance
“…The recent demonstration that MPMs are in fact polyclonal tumors formed by the coalescence of different independent subclones highlights the need for new therapeutic approaches, as each clone may carry its own distinct set of molecular alterations, and the intratumoral heterogeneity arising may allow for the emergence of drug-resistant subpopulations, and as such multi-targeted approaches to therapy may be required to overcome the issue of clonality (37). EZH2 is associated with the H3K27me3 histone post-translational modification mark common to silenced chromatin or bivalent 'poised' promoters (20,38). The lysine demethylases that catalyze the removal of this mark have been identified as Kdm6a (Utx) and Kdm6b (Jmjd3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent demonstration that MPMs are in fact polyclonal tumors formed by the coalescence of different independent subclones highlights the need for new therapeutic approaches, as each clone may carry its own distinct set of molecular alterations, and the intratumoral heterogeneity arising may allow for the emergence of drug-resistant subpopulations, and as such multi-targeted approaches to therapy may be required to overcome the issue of clonality (37). EZH2 is associated with the H3K27me3 histone post-translational modification mark common to silenced chromatin or bivalent 'poised' promoters (20,38). The lysine demethylases that catalyze the removal of this mark have been identified as Kdm6a (Utx) and Kdm6b (Jmjd3).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis of MPM, a subset of genes was found to be silenced by histone H3 lysine 27 trimethylation (H3K27me3), a mark most often found at or near the promoters of silent genes (20,21). Polycomb repressive complex 2 (PRC2) catalyses tri-methylation of Histone H3 at lysine 27 (H3K27me2/3) (22), and contains the lysine methyltransferase EZH2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, HP1 promotes tumor suppressor BRCA1 functions during the DNA damage response [36]. The trimethylation of histone H3 lysine 27 (H3K27me3) contributes to gene repression [37]. NF-κB is involved in inflammation and tumor growth [38].…”
Section: Discussionmentioning
confidence: 99%
“…We were interested in the mechanism by which deoxycholate or C. scindens increased GMPs. Due to the persistent nature of immunity to E. histolytica following bone marrow transplant we examined the epigenetic mediator JMJD3 (21,29) . C. scindens colonization or deoxycholate administration increased expression of JMJD3 specifically in sorted GMPs (Figure 3 A, QPCR of sorted marrow GMPs demonstrated that genes associated with histone H3, including the demethylase JMJD3 are enriched in mice exposed to C. scindens (Figure S3 A, B, C,).…”
Section: Main Textmentioning
confidence: 99%